Bridging Digital Service Gaps: Integrating Chatbots and Product Catalogs in BUMDes Baturiti - Sudrajat, Kadek; Cahyono, Irfan; Pratama, Putu Yogi Agustia; Mahadipta, Ngurah Gede Dwi; Wicaksana, GDA; Bohm, Fabian; Lovas, Tibor (Jurnal Pengabdian Kepada Masyarakat MEMBANGUN NEGERI, 2025)
Digital transformation has become an essential driver for improving public service quality in Village-Owned Enterprises (BUMDes). However, many BUMDes still rely on manual information services, resulting in slow responses, limited accessibility, and low visibility of local products. This study addresses these challenges by examining the integrated implementation of chatbot technology and a digital product catalog on the BUMDes Baturiti website. A qualitative single case study approach was employed, involving in-depth interviews, participatory observation, and conversation log analysis conducted from January to June 2025. The findings reveal that chatbot adoption significantly enhances service efficiency through real-time automated responses, while the digital product catalog increases product visibility and market reach. The integration of both technologies reduces service complaints from 10 to 3 cases per month and increases user satisfaction to 85 percent for chatbot features and 80 percent for the product catalog. Key success factors include technological readiness, human resource capacity, stakeholder collaboration, and adequate infrastructure. This study contributes a practical model for digital service innovation in rural economic institutions and demonstrates how integrated digital solutions can strengthen transparency, accountability, and public trust in BUMDes operations.